Palliative Care: A Primary Care Pharmacist Perspective - Julia Bognar (MDPI AG, 2022)
The overview approaches pharmacy practice in palliative care from a global viewpoint and aims to provide insight into front-line pharmacist-patient relationships by sharing case studies and personal experiences.